Small nucleolar RNA is potential as a novel player in leukemogenesis and clinical application - Li-Min Lin (Wolters Kluwer Health, 2021)
Abstract. Lack of clarity of the mechanisms that underlie leukemogenesis obstructs the diagnosis, prognosis, and treatment of leukemia. Research has found that small nuclear RNA (snoRNA) plays an essential role in leukemia. These small non-coding RNAs are involved in ribosome biogenesis, including the 2′-O-methylation and pseudouridylation of precursor ribosomal RNA (pre-rRNA), and pre-rRNA splicing. Recently, many snoRNAs were found to be orphans that have no predictable RNA modification targets, but these RNAs have always been found to be located in different subcellular organelles, and they play diverse roles. Using high-throughput technology, snoRNA expression profiles have been revealed in leukemia, and some of the deregulated snoRNAs may regulate the cell cycle, differentiation, proliferation, and apoptosis in leukemic cells and confer drug resistance during leukemia treatment. In this review, we discuss the expression profiles and functions of snoRNAs, particularly orphan snoRNAs, in leukemia. It is possible that the dysregulated snoRNAs are promising diagnosis and prognosis markers for leukemia, which may serve as potential therapeutic targets in leukemia treatment.